Interactive Digital Platforms and Artificial Intelligence Applications to Develop Technological Innovation Skills among Saudi University Students - Abdelmagid, Ahmed Sadek; Hafez, Mohamed Ahmed; Ahmed, Eman Wefky; Jabli, Naif Mohammed; Ibrahim, Asem Mohammed; Teleb, Ahmed Ali; Aljawarneh, Nader Mohammad (International Journal of Interactive Mobile Technologies (iJIM), 2024)
In this paper, we investigate the efficacy of an edX-based learning technology and learning environment augmented with artificial intelligence (AI) applications in fostering technological innovation skills among university students. A quasi-experimental design was employed, involving two groups of bachelor’s degree students (n = 57) from the College of Education at King Khalid University. The experimental group (n = 28) utilized the edX platform with integrated AI features, while the control group (n = 29) employed the traditional Blackboard platform. Both groups participated in the “Using Computers in Education” course. A pre-post assessment of technological innovation skills was conducted, and the data were analyzed using an independent sample t-test. Results revealed a statistically significant difference in skill development between the groups, favoring the edX platform with AI integration. These findings suggest that using blended learning environments may have the potential to enhance students’ technological innovation capabilities.